Hydrogen peroxide toxicity on auditory cells: An in vitro study. (25th August 2021) - Gentilin, Erica; Cani, Alice; Simoni, Edi; Chicca, Milvia; Di Paolo, Maria Luisa; Martini, Alessandro; Astolfi, Laura
Abstract: In recent decades, interest has increased in the role of reactive oxygen species (ROS) in health and disease. The ROS are key causative factors in several hearing loss pathologies including ototoxicity, noise trauma, cochlear ageing and ischemic injury. In order to investigate ROS effects on inner ear cells and counteract them, we developed an in vitro model of oxidative stress by exposing the inner ear cell line OC-k3 to hydrogen peroxide (H2 O2 ) at concentrations able to affect in vivo cellular components but allowing cell survival. The treatment with high concentrations (20 and 30 μM) resulted in reduction of cell viability, activation of apoptosis/necrosis and alteration of morphology, cell cycle progression and antioxidant defences. The ROS effects in inner ear cells are difficult to assess in vivo . Organocultures may provide preservation of tissue architecture but involve ethical issues and can be used only for a limited time. An in vitro model that could be commercially available and easy to handle is necessary to investigate inner ear oxidative stress and the ways to counteract it. The OC-k3 line is a suitable in vitro model to study ROS effects on inner ear cells because the observed cell alterations and damages were similar to those reported in studies investigating ROS effects of ototoxic drugs, noise trauma and cochlear ageing. Graphical abstract: Image 1 Highlights: H2 O2 reduced cell viability and altered inner ear cell morphology. H2 O2 activated cell death mechanism. H2 O2 altered cell cycle progression. H2 O2 altered antioxidant defences.